Analyzing University Students’ Learning Needs to Improve English Presentation Skills - Marsella, Elisabeth; Citrayasa, Vinindita (Institut Agama Islam Negeri Palopo, 2024)
Presentation skills are essential to public speaking, which is part of English learning. Regarding its importance, the English presentation usually focuses on language production and general presentation skills. This can be ineffective since there are many aspects of presentation skills. To make it more efficient, a need analysis should be done to find out which skills learners still find difficult. Therefore, this study tries to find what presentation skills should be prioritized in English learning. To respond to the problem, a survey was conducted by distributing a questionnaire to 149 university students from the Informatics department. The result showed that the top 5 most difficult aspects are engaging the interest of the audience, speaking clearly/pronunciation, handling the audience questions, getting the timing right, and putting thoughts/ideas into speech. In terms of the skill dimension, verbal and nonverbal communication is considered the most difficult. This finding should be taken into account when designing English learning activities.